Non-Helicobacter pylori Gastric Intestinal Metaplasia in Children: A Series of Cases and Review of the Literature - Sandra Mabel Camacho-Gomez; Anas Bernieh; Ali G. Saad; Neelesh Ajit Tipnis (Case Reports in Gastrointestinal Medicine)
In the pediatric population, Gastric Intestinal Metaplasia (GIM) is a finding with unknown frequency and, more importantly, unknown clinical implications. The relationship between Helicobacter pylori (HP) infection and GIM is well documented, as well as an association between duodenogastric reflux and GIM. We present two cases of pediatric patients with GIM along with a review of the literature. The diagnosis of GIM may have adverse clinical implications and should be made with caution in a child. The association of GIM and adenoma/dysplasia and carcinoma is rarely seen in children, primarily because the time required for these to develop takes the individual into adulthood. Treatment, long-term consequences, and surveillance protocols are not well established in the pediatric population. Studies to evaluate the long-term natural history, treatment, and surveillance protocols in children with GIM are needed.